DEVELOPMENT OF DIALOGICAL SPEECH IN TEACHING RUSSIAN LANGUAGE - Raxmanova G. G. (Western European Studies, 2024)
this article examines the problems of teaching Russian as a foreign language, the development of speech and mental development of students, teaching elementary grammar skills, the development of dialogical speech as the main form of verbal communication. Participation in dialogue is carried out through dialogical speech, the mastery of which is a condition for the full development of the student and his activity in communicating with others.
Keywords: coherent speech; dialogical speech; dialogue; communication